An explorative study of the individual differences associated with consumer stockpiling during the early stages of the 2020 Coronavirus outbreak in Europe. (1st December 2020) - Dammeyer, Jesper
Abstract: There is little existing research on why some people stockpile goods and others do not at a time of crisis. More research on this phenomenon and the individual differences associated with it is needed in order to gain a better understanding of what is a potentially economically and socially disruptive behavior. In this study, 175 adult participants from Denmark and 90 from the United Kingdom responded to a survey about the activity of extra shopping (stockpiling) during the first weeks of the Coronavirus outbreak. Questions exploring the "big five" personality traits, Social Dominance Orientation, Health Literacy, and attitudes to the governmental response to the crisis were included in the survey. The explorative analysis showed that stockpiling was associated with high scores on Extraversion and Neuroticism, and low scores on Conscientiousness and Openness to Experience. Stockpiling was also associated with the view that the government should be doing more to stop the Coronavirus epidemic. An explorative factor analysis of reasons for stockpiling identified the two factors "Panic" and "Action".